Synthesis and characterization of d5‐barbarin for use in barbarin‐related research. Issue 1 (23rd August 2022) - Kudrimoti, Sucheta; Machin, Jacob; Arojojoye, Adedamola S.; Awuah, Samuel G.; Eisenberg, Rodney; Fenger, Clara; Maylin, George; Lehner, Andreas F.; Tobin, Thomas
Abstract: Based on structural similarities and equine administration experiments, Barbarin, 5‐phenyl‐2‐oxazolidinethione from Brassicaceae plants, is a possible source of equine urinary identifications of aminorex, ( R, S )‐5‐phenyl‐4, 5‐dihydro‐1, 3‐oxazol‐2‐amine, an amphetamine‐related US Drug Enforcement Administration (DEA) controlled substance considered illegal in sport horses. We now report the synthesis and certification of d 5 ‐barbarin to facilitate research on the relationship between plant barbarin and such aminorex identifications. D 5 ‐barbarin synthesis commenced with production of d 5 ‐2‐oxo‐2‐phenylacetaldehyde oxime ( d 5 ‐oxime) from d 5 ‐acetophenone via butylnitrite in an ethoxide/ethanol solution. This d 5 ‐oxime was then reduced with lithium aluminum hydride (LiAlH4 ) to produce the corresponding d 5 ‐2‐amino‐1‐phenylethan‐1‐ol ( d 5 ‐ phenylethanolamine). Final ring closure of the d 5 ‐phenylethanolamine was performed by the addition of carbon disulfide (CS2 ) with pyridine. The reaction product was purified by recrystallization and presented as a stable white crystalline powder. Proton NMR spectroscopy revealed a triplet at 5.88 ppm for one proton, a double doublet at 3.71 ppm for one proton, and double doublet at 4.11 ppm for one proton, confirming d 5 ‐barbarin as the product. Further characterization by high resolution mass spectrometry supports the successful synthesis of d 5 ‐barbarin. Purity of the recrystallized product was ascertained by High Performance Liquid Chromatography (HPLC) to be greater than 98%. Together, we have developed the synthesis and full characterization of d 5 ‐barbarin for use as an internal standard in barbarin‐related and equine forensic research. Abstract : We now report the synthesis of d 5 ‐barbarin for use in research concerning the role of barbarin in glucobarbarin‐related identifications of aminorex in experimental and postcompetitive event urine samples from horses fed plants containing glucobarbarin. We also propose a synthetic pathway for aminorex formation from glucobarbarin.